Penerapan Metode Simple Additive Weighting (SAW) dan Tabel Keputusan pada Sistem Pendukung Keputusan Menentukan Tingkat Punishment Siswa Bermasalah - Purwanto, Riyadi; Novia Prasetyanti, Dwi; Hafsarah Maharrani, Ratih; Syafirullah, Lutfi (P3M Politeknik Negeri Cilacap, 2021)
RETRACTED Following a rigorous, carefully concerns and considered review of the article published in Infotekmesin to article entitled â€œPenerapan Metode Simple Additive Weighting (SAW) dan Tabel Keputusan pada Sistem Pendukung Keputusan Menentukan Tingkat Punishment Siswa Bermasalah â€ Vol 12, No 2, pp.115-121, July 2021, DOI: https://doi.org/10.35970/infotekmesin.v12i2.780 This paper has been retracted at the request of the author of this article because by mistake the same article has been published in another journal publisher. The article contained redundant material, the paper published in Proceedings of the 4th International Conference on Applied Science and Technology on Engineering Science - iCAST-ES, ISBN 978-989-758-615-6; ISSN 2975-8246, pages 1194-1202. DOI: 10.5220/0010962300003260, The document and its content has been removed from Infotekmesin, and reasonable effort should be made to remove all references to this article.